1999
DOI: 10.1159/000015958
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Intracranial Hemorrhage when Aspirin Is Combined with Warfarin: A Meta-Analysis and Hypothesis

Abstract: Background: Oral anticoagulation with vitamin K antagonists increases the risk of intracranial hemorrhage; whether addition of aspirin to oral anticoagulation augments this risk is unclear. Methods: Meta-analysis of randomized clinical trials in which aspirin was added to oral anticoagulants. Results: Six randomized clinical trials were identified, including a total of 3,874 participants. Use of aspirin with oral anticoagulants was associated with more than double the frequency of intracranial hemorrhage (rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(67 citation statements)
references
References 12 publications
4
59
0
4
Order By: Relevance
“…12 In addition, combining aspirin with an oral anticoagulant at higher anticoagulation intensities may increase the risk and severity of intracranial hemorrhage, particularly in elderly patients. 13 (Refs. from long format guidelines.)…”
Section: Proof Of the Efficacy Of Anticoagulationmentioning
confidence: 99%
“…12 In addition, combining aspirin with an oral anticoagulant at higher anticoagulation intensities may increase the risk and severity of intracranial hemorrhage, particularly in elderly patients. 13 (Refs. from long format guidelines.)…”
Section: Proof Of the Efficacy Of Anticoagulationmentioning
confidence: 99%
“…Statistical methodology helps to minimize these confounders to some extent, however the age difference between study groups was definitive: non-APAC age group averaged 50.6 years, compared to the APAC group of 71.7 years. In addition, many of the patients on clopidogrel were on more than one agent, which is a known risk factor for ICH [11] [15]- [17]. There were only 9 patients taking clopidogrel as a single agent, making statistical analysis underpowered when looking at clopidogrel alone; thus the results of this study may be best looked at in terms of dual antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is not uncommon for patients to be placed on a dual or even a triple regimen of APAC medications. The combined use of two or more medications appears to carry a greater risk of spontaneous ICH than does the use of single agents [11] [15]- [17]. Given the increasing use of APACs [1]- [5] and the rapid development of newer agents, the neurosurgical implications are significant.…”
Section: Introductionmentioning
confidence: 99%
“…This metaanalysis showed that adjusted-dose warfarin is remarkably effective in reducing the risk of stroke for patients with AF. 92 Compared with placebo, adjusted-dose warfarin decreased the relative risk of stroke by 62% (95% confidence interval [CI], 48%-72%). 82 The absolute reduction of stroke risk by adjusted-dose warfarin vs placebo was 2.7% annually for primary prevention and 8.4% annually for secondary prevention.…”
Section: Preventing Stroke In Patients With Afmentioning
confidence: 99%
“…Using aspirin in addition to warfarin has been found to increase elderly patients' absolute risk of serious bleeding by 0.6% during a 90-day observation period and to increase their relative risk of intracranial hemorrhage by a factor of 2.4. 92,103 For patients with chronic stable coronary artery disease and AF, adjusted-dose warfarin without aspirin is probably sufficient. 3,104 Observational data suggest that the combination of aspirin, clopidogrel, and warfarin may be associated with a high risk of bleeding.…”
Section: Preventing Stroke In Patients With Afmentioning
confidence: 99%